2005
DOI: 10.1111/j.1742-1241.2005.00674.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving glucose management: Ten steps to get more patients with type 2 diabetes to glycaemic goal

Abstract: Despite increasingly stringent clinical practice guidelines for glycaemic control, the implementation of recommendations has been disappointing, with over 60% of patients not reaching recommended glycaemic goals. As a result, current management of glycaemia falls significantly short of accepted treatment goals. The Global Partnership for Effective Diabetes Management has identified a number of major barriers that can prevent individuals from achieving their glycaemic targets. This article proposes 10 key pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
100
0
11

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(116 citation statements)
references
References 80 publications
5
100
0
11
Order By: Relevance
“…The use of statins and effective anti-hypertensive treatment should be initiated irrespective of previous CV events in all diabetic patients. However, a true shift in treatment strategy for type 2 diabetes will require the implementation of appropriate treatment at the time of the diagnosis [40], if not earlier on. The probability of there being existing diabetic complications is lower at diagnosis, allowing effective protection.…”
Section: Discussionmentioning
confidence: 99%
“…The use of statins and effective anti-hypertensive treatment should be initiated irrespective of previous CV events in all diabetic patients. However, a true shift in treatment strategy for type 2 diabetes will require the implementation of appropriate treatment at the time of the diagnosis [40], if not earlier on. The probability of there being existing diabetic complications is lower at diagnosis, allowing effective protection.…”
Section: Discussionmentioning
confidence: 99%
“…[4,5] Structured and regular review of diabetics have shown to be effective in improving the process of their care. [6,7] Reports have shown positive outcomes from utilizing register-recall systems such as improvement in glycemic control, quality of life, as well as in the number of recommended laboratory screening. [3,[6][7][8][9][10] The majority of primary care clinics in Saudi Arabia are walk-in clinics that are supported by secondary or tertiary care hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] Reports have shown positive outcomes from utilizing register-recall systems such as improvement in glycemic control, quality of life, as well as in the number of recommended laboratory screening. [3,[6][7][8][9][10] The majority of primary care clinics in Saudi Arabia are walk-in clinics that are supported by secondary or tertiary care hospitals. Although computerized systems are widely utilized in sending reminders to patients for scheduled appointments, a register-recall system that periodically identifies patients not meeting their treatment targets (e.g., uncontrolled diabetes) and actively recalls them for review is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, this includes achieving as near-optimal glycemic control as possible without increasing hypoglycemia and other treatment-related complications. However, achieving glycemic targets remains a challenge in many people with type 2 diabetes (T2D) [3][4][5][6] . In most people with T2D, insulin therapy will be required in time to supplement the progressive loss of -cell function, but starting insulin therapy is often delayed due to barriers, including fear of hypoglycemic events and weight gain, resistance to changes in regimens, and higher treatment costs compared with non-insulin therapy 7 .…”
Section: Introductionmentioning
confidence: 99%